(untitled) (Conferencea, 2024)
Today, higher education is important not only for the social and economic development of the society, but also for the fact that it closely supports the formation of an innovative economy. In the concept of development of higher education in the country until 2030: "increasing the coverage of higher education, ensuring a healthy competitive environment, ensuring academic and financial independence of higher education institutions, gradual transition to the self-financing system and ensuring financial stability, education, science, innovation and Step-by-step implementation of the "University 3.0" concept, which implies the inextricability of the commercialization of scientific research results, broad attraction of foreign investments, expansion of the scope of paid services and other non-budgetary funds at the expense of technopark, foresight, transfer of technologies, start-up, accelerator in higher education institutions A number of priority tasks have been defined as "establishing centers and bringing them to the level of scientific and practical institutions that research and forecast the socio-economic development of the relevant industry, sector and regions".